Controlled Clinical Comparison of Plastic versus Glass Bottles of BacT/ALERT PF Medium for Culturing Blood from Children - Petti, Cathy A. (American Society for Microbiology, 2005)
The plastic pediatric BacT/ALERT (bioMérieux, Durham, N.C.) PF (PPF) is a new nonvented aerobic culture medium in a clear plastic bottle designed to prevent breakage. We compared the performance of the new PPF bottle to that of the present glass BacT/ALERT PF bottle for the recovery of microorganisms as well as for the time to detection of growth in samples of blood obtained for culture from children. We found that the PPF and PF bottles were comparable for recovery of microorganisms and that the safety advantage of plastic bottles can be achieved without compromising performance.